The supply chain revolution innovative sourcing and logistics for a fiercely competitive world - Sarkar, Suman (AMACOM, 2017)
Across a range of industries, once-leading companies are in trouble: Walmart, IBM, Pfizer, HP, and The Gap to name a few. But others are thriving. The difference is how the company's leaders view their supply chain: Is it just about cutting cost or do they see its hidden tools for outperforming the competition?Steve Jobs, upon returning to Apple in 1997, focused on transforming the supply chain. He hired Tim Cook--and the company sped up the development of new products, getting them into consumers' hands faster. The rest is history. While competitors were shutting stores, Zara's highly responsive supply chain made it the most valued company in the retail space and its founder, the richest man in Europe.Showcasing real solutions learned from true success stories like these and many others, The Supply Chain Revolution provides for business leaders the secrets to succeeding in a disruptive world. They will learn to:• Make alliances more successful• Simplify and debottleneck the supply chain• Boost retail success by managing store investment• Improve customer satisfaction and increase revenue• And more!Every year, more businesses fail because of their old-school views toward cutting costs, and they usually begin with the supply chain. Don't go down with that ship! Discover how the right supply chain can actually help you thrive